Occurrence of ESCHERICHIA COLI O157 in a river used for fresh produce irrigation in Nigeria (International Journal of Irrigation and Water Management, 2016)
Concerns about the persistence of ESCHERICHIA COLI O157 in irrigation waters and its transmission to fresh produce makes investigation of irrigation waters imperative. The prevalence of this pathogen and seasonal levels of water quality parameters in Kubanni River were studied, using standard methods, over a 10-month period. Detection rate for E. COLI O157 confirmed by slide agglutination was 2.1%. Faecal coliform counts (FCC) exceeded acceptable limits and was significantly higher in the dry season than during the rainy season (p